Effect of Lysozymes, Antibiotics and Probiotics on Growth Performance and Biochemical Parameters in Broiler Chickens - Baksi, Surajit; Chauhan, Pravin Singh; Rao , Nirav; Chauhan, Ashish (International Journal of Livestock Research, 2019)
The objective of present study was to determine the comparative effect of lysozymes with enrofloxacin and Lactobacillus as growth promoters in broiler chickens. Two hundred-day old broilers were selected and randomly divided into four treatment groups. Each group had five repeats with 10 birds in each replication. Treatments with lysozyme, enrofloxacin and Lactobacillus improved the growth performance, but feed conversion ratio was poor. Body weight and feed conversion ratio were increased by 2.94% and 2.91%, respectively in lysozyme supplemented group as compared to control group. It was more or less similar with enrofloxacin and Lactobacillus supplemented group. Biochemical parameters (activity of lysozyme, total protein, blood glucose, cholesterol, AST and GPT) of birds were also measured and it was observed that lysozymes improved the health performance and immune functions of broiler chickens and can be used as an alternative to growth promoters like antibiotics and probiotics.